Information technology in the development of the Polish construction industry - Kapliński, Oleg (Technological and Economic Development of Economy, 2009)
The utilization of Construction Management (CM) tools and Information Technology (IT) is the object of the paper. A review of the problems of usefulness of IT solutions on offer in Polish construction sector is presented. Generally, changes in approach to information technology, diversification and variety of its software, prosperity in construction industry and its solutions are the main motif of this paper. A significant discrepancy in the assessment of attractiveness and usefulness of those methods by businessmen and academics has been pointed out. Relationships between prosperity in construction market and usage of new planning methods, decision making, and IT systems are discussed. Results of studies are negative. The reasons for such a state of things have been presented. The research was based on questionnaires and interviews. Regression and correlation were used for the analysis. Besides, an attempt to describe the phenomenon of saturation of Polish construction sector with IT tools has been indicated. The discussion of those problems may be addressed to potential IT suppliers and can be implemented in different construction sectors. Informacinės technologijos ir Lenkijos statybos pramonės plėtra Santrauka. Straipsnio objektas – statybos valdymo priemonių ir informacinių technologijų (IT) naudojimas. Iškeliamos Lenkijos statybos sektoriui siūlomų informacinių technologijų sprendimų naudingumo problemos. Pagrindinis straipsnio atsiradimo motyvas – kintantis požiūris į informacines technologijas, programinės įrangos įvairovė ir diversifikacija bei statybos pramonės klestėjimas. Verslininkų ir mokslininkų vertinimai minėtų technologijų patrauklumo ir naudingumo požiūriu labai skiriasi. Aptariama, ar suklestėjimas statybos rinkoje priklauso nuo naujų planavimo ir sprendimų priėmimo metodų bei informacinių technologijų naudojimo. Tyrimai pateikia neigiamą atsakymą ir paaiškina to priežastis. Tyrimas paremtas anketavimu ir interviu ėmimu. Tyrimams pritaikytos regresinė ir koreliacinė analizės. Be to, pabandyta atskleisti, kiek statybos sektorius yra prisotintas informacinėmis technologijomis. Šių problemų aptarimas gali būti naudingas informacinių technologijų teikėjams ir pritaikytas įvairiose statybos srityse. Reikšminiai žodžiai: statybos pramonė, Lenkija, statybos valdymo priemonės, IT evoliucija, IT priemonių naudojimas, prisotinimas IT priemonėmis. First published online: 21 Oct 2010